PENGARUH MOTIVASI KERJA DAN PRAKTIK KERJA LAPANGAN TERHADAP KESIAPAN KERJA MAHASISWA STMIK SINAR NUSANTARA SURAKARTA - Ari Wibowo; Bambang Satrio Nugroho (JURNAL ILMIAH EDUNOMIKA, 2021)
One indicator of higher education outcomes that must be achieved is the percentage of graduates who find work . The purpose of this study was to measure and examine the effect of work motivation and fieldwork practices on job readiness of STMIK Sinar Nusantara Surakarta students. The number of samples in this study were 50 respondents, the sampling technique used purposive sampling. The results of the regression analysis found that there was a positive and significant influence on work motivation variables and field work practices on student work readiness. The result is that the variables of work motivation and field work practice significantly and positively affect student work readiness with path coefficient values (β) 0.388 and 0.334. SmartPLS also produces a determination coefficient value of 40.6% Exogenous variables affect endogenous variables.